2021
DOI: 10.1097/rct.0000000000001206
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Feasibility of Ultrashort Echo Time T2* Cartilage Mapping in the Sacroiliac Joints

Abstract: PurposeAssess feasibility of ultrashort echo time (UTE) T2* cartilage mapping in sacroiliac (SI) jointsMethodsProspective magnetic resonance imagings with UTE T2* cartilage maps obtained on 20 SI joints in 10 subjects. Each joint was segmented into thirds by 2 radiologists. The UTE T2* maps were analyzed; reliability and differences in UTE T2* values between radiologists were assessed.ResultsMean UTE T2* value was 10.44 ± 0.60 ms. No difference between right/left SI joints (median, 10.52 vs 10.45 ms; P = 0.940… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that T2 relaxation times of the SIJ cartilage were significantly higher in patients with axSpA than in healthy controls ( 11 , 38 ). SIJ cartilage T2* values of different anatomical regions were not compared in our study because a previous study found there to be no substantial differences across regions in healthy volunteers ( 15 ). The reproducibility of the UTE-T2* measurements of the SIJ cartilage in our study was good, although ROIs may be influenced by the partial volume effect of adjacent bone or ligamentous structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that T2 relaxation times of the SIJ cartilage were significantly higher in patients with axSpA than in healthy controls ( 11 , 38 ). SIJ cartilage T2* values of different anatomical regions were not compared in our study because a previous study found there to be no substantial differences across regions in healthy volunteers ( 15 ). The reproducibility of the UTE-T2* measurements of the SIJ cartilage in our study was good, although ROIs may be influenced by the partial volume effect of adjacent bone or ligamentous structures.…”
Section: Discussionmentioning
confidence: 99%
“…Signals from the short T2* components of the articular cartilage are poorly captured by long TE sequences, which may be useful in determining early cartilage abnormalities ( 13 , 14 ). Although one study reported that 3D-UTE T2* mapping is feasible for SIJ cartilage imaging in asymptomatic volunteers ( 15 ), to the best of our knowledge, 3D-UTE T2* mapping in patients with axSpA has not yet been examined. Therefore, we conducted this study to assess the feasibility of the 3D-UTE sequence for detecting SIJ bone erosion in patients with axSpA using CT as a reference, to evaluate the quantitative T2* mapping from the 3D-UTE sequence in the diagnosis of axSpA, and to compare its performance with that of conventionally clinically available GRE-T2* mapping.…”
Section: Introductionmentioning
confidence: 99%